The Double “Others” under Gender Oppression and Colonial Cultural Conflicts in The Piano - Song, Yanke (International Journal of Social Sciences and Public Administration, 2025)
This paper explores the complex intersection of gender oppression and colonial cultural conflicts in Jane Campion’s The Piano (1993), focusing on the protagonist Ada’s dual “Other” identity in a colonial context. As a Scottish immigrant woman in 19th-century New Zealand, Ada experiences both gender-based subjugation under patriarchal norms and cultural marginalization as an outsider in colonial society. Using Homi K. Bhabha’s theory of “cultural hybridity” and “Third Space”, the study analyzes how Ada resists oppression through the piano, a symbol that becomes her emotional outlet and a medium for constructing cultural identity. Ada’s silence challenges traditional gender roles, while the piano serves as a “Third Space” where she survives between colonial and indigenous cultures. The paper highlights Ada’s process of “mimicry and distortion”-imitating societal expectations of women while subverting them through musical expression-and critiques the film’s Eurocentric narrative that sidelines Māori women’s experiences. Ultimately, The Piano exemplifies how female identity under colonialism is shaped by dual oppressions, and how cultural hybridity enables resistance and self-formation. Ada’s story underscores the power of art and silence as tools for reclaiming agency in patriarchal and colonial contexts.